The Antibacterial Effect of Boron Compounds and Evaluation of the Effects on Biofilm Formation in the Infection Model of Klebsiella pneumoniae on the HepG2 Cell Line - Serkan Yıldırım; Mustafa Can Güler; Sümeyye Başer; Ali Taghizadehghalehjoughi; Demet Çelebi; Özgür Çelebi (Journal of Contemporary Medicine, 2023)
Aim: Klebsiella pneumoniae causes hospital-acquired pneumonia, urinary tract infection and bacteremia in immunocompromised patients. Klebsiella pneumoniae, which has become more common recently, causes antibiotic resistance as well as pyogenic liver abscesses and hematogenous metastatic spread in humans. Developing antibiotic resistance complicates the treatment of liver infections. In our study, we aimed to evaluate the effect of boron compounds in an infection model created by Klebsiella pneumoniae 700603. Materials and Methods: Minimum inhibitory concentration and fractional inhibitory concentration studies, resistance gene levels, and HepG2 cell analyses were performed and evaluated. Results: We determined the low and high minimum inhibitory concentration values of boron components, sodium perborate monohydrate and etidote, respectively. In addition, sodium perborate monohydrate is also effective on biofilm formation. Our findings have shown that boron compounds are more effective when used in a combination. In the toxicity model created in the cellular study, the boron compounds cytotoxic effect decreased due to their antibacterial effects. Conclusion: İt seems that boron compounds are effective, and the positive effect increases when used together.